2020
DOI: 10.1186/s12943-020-01204-7
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of RNA N6-methyladenosine in Cancer progression

Abstract: N6-methyladenosine (m6A) is considered the most common, abundant, and conserved internal transcript modification, especially in eukaryotic messenger RNA (mRNA). m6A is installed by m6A methyltransferases (METTL3/14, WTAP, RBM15/15B, VIRMA and ZC3H13, termed “writers”), removed by demethylases (FTO, ALKBH5, and ALKBH3, termed “erasers”), and recognized by m6A-binding proteins (YTHDC1/2, YTHDF1/2/3, IGF2BP1/2/3, HNRNP, and eIF3, termed “readers”). Accumulating evidence suggests that m6A RNA methylation greatly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
587
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 689 publications
(588 citation statements)
references
References 161 publications
1
587
0
Order By: Relevance
“…As aforementioned, m 6 A modification is a dynamic and reversible epigenetic change ( Zhang et al, 2020 ), which affects the stability and function of RNAs, thereby modulating the pathogenesis and progression of diseases ( Qin et al, 2020 ; Wang et al, 2020 ; Zhu et al, 2020 ). M 6 A modification has been identified in more than 7,000 human genes, and it preferentially occurred at the site of stop codons and long internal exons within the RRACH sequence (R = G or A; H = A, C, or U) ( Dominissini et al, 2012 ).…”
Section: Rna M 6 a Modificationmentioning
confidence: 99%
“…As aforementioned, m 6 A modification is a dynamic and reversible epigenetic change ( Zhang et al, 2020 ), which affects the stability and function of RNAs, thereby modulating the pathogenesis and progression of diseases ( Qin et al, 2020 ; Wang et al, 2020 ; Zhu et al, 2020 ). M 6 A modification has been identified in more than 7,000 human genes, and it preferentially occurred at the site of stop codons and long internal exons within the RRACH sequence (R = G or A; H = A, C, or U) ( Dominissini et al, 2012 ).…”
Section: Rna M 6 a Modificationmentioning
confidence: 99%
“…RNA methylation plays an important role in many biological processes and is widely involved in human development and disease occurrence [49]. N6-methyladenosine (m6A) is a conserved internal modi cation of most eukaryotic nuclear RNA, which is closely related to the splicing , stability and translation e ciency of mRNA and noncoding RNA [28,50].With further studies, M6A can catalyse the M6A modi cation in the mRNA of oncogenes or tumor suppressor genes,and recognize the changes through molecular biological mechanism to regulate the expression of oncogene and tumor suppressor gene [51].The evidence showed that the change of m6A level was involved in the occurrence and development of tumor by affecting the expression of tumor-related genes BRD4, SOCS2 and EGFR [52].…”
Section: Discussionmentioning
confidence: 99%
“…Inserting information beyond the information carried by their base sequences to gene transcripts, altering the charge of RNA bases and their matching properties, differential folding of RNAs, and the formation of a regulatory protein-RNA interaction recognition element are classical transcriptome modification processes. Therefore, these modifications are involved in the whole process of RNA metabolism, regulating the fine expression patterns of genes and, ultimately, affecting the biological behaviour of cells [11,12].…”
Section: Origin Of M6a Modificationmentioning
confidence: 99%